Harnessing heterosis and male sterility in soybean [Glycine max (L.) Merrill]: A critical revisit - Ramlal, Ayyagari; Nautiyal, Aparna; Baweja, Pooja; Kumar Mahto, Rohit; Mehta, Sahil; Pujari Mallikarunja, Bingi; Vijayan, Roshni; Saluja, Shukla; Kumar, Vijay; Kumar Dhiman, Sunil; Lal, S. K.; Raju, Dhandapani; et al. (Frontiers in Plant Science, 2022)
Soybean is a predominantly self-pollinated, crop. It is also one of the important oilseed legumes. Soybean is an excellent crop having industrial, traditional, culinary, feeding, and cultural roles. Genetic diversity in breeding programs is of prime importance as it ensures the success of any breeding by enhancing the outcomes and results of the plants. The phenomenon wherein the progeny exhibits greater biomass (yield), and a faster rate of development and fertility than its parents is referred to as heterosis. As of now, heterosis is mainly limited to the trait of seed yield. Heterosis is considered the basis for the development of better (superior) varieties. Male sterility is extensively used for the production of seeds and improvement of crops coupled with the traditional breeding programs and molecular technology. Therefore, deployment of male sterility and heterosis in breeding soybean could yield better outcomes. This review aims to focus on two aspects namely male sterility and heterosis in soybean with its scope for crop improvement.